DISTRIBUSI JENIS KONTRASEPSI BERDASARKAN USIA DAN PARITAS AKSEPTOR DI PUSKESMAS WANADADI 1 - Durotun Naviah; Arlyana Hikmanti; Fauziah Hanum Nur Adriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Population growth requires effective control through the Family Planning (FP) program by promoting the appropriate use of contraceptive methods according to the characteristics of family planning acceptors, particularly age and parity. This study aimed to determine the distribution of contraceptive methods based on the age and parity of family planning acceptors at Wanadadi 1 Public Health Center. This study employed a quantitative method with a descriptive design. Data were collected retrospectively using a master table derived from secondary data obtained from the 2025 Family Planning Service Register at Wanadadi 1 Public Health Center. The sampling technique used was total sampling involving 417 family planning acceptors. Data were analyzed using univariate analysis and presented as frequency distributions and percentages. The results showed that the majority of acceptors were aged >35 years (207 acceptors; 49.64%), while most were multiparous (2–4 children) with 306 acceptors (73.38%). Overall, hormonal contraceptive methods were the most commonly used by 338 acceptors (81.05%), with injectable contraception being the most frequently selected method by 181 acceptors (43.41%), followed by contraceptive implants used by 150 acceptors (35.97%). Implants were the most frequently used contraceptive method among acceptors aged <20 years and 20–35 years, whereas injectable contraception predominated among those aged >35 years. Based on parity, injectable contraception was the most commonly used method among primiparous, multiparous, and grand multiparous acceptors. In conclusion, the use of contraceptive methods at Wanadadi 1 Public Health Center was predominantly hormonal, particularly injectable contraception, across all age groups and parity categories.